KONSEP STRATEGI THEISTIC SPIRITUAL DALAM LAYANAN BIMBINGAN KONSELING DAN PSIKOTERAPI ISLAM - Istiani, Nurul; Zaduqisti , Esti (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2017)
In the teachings of Islam, the psychological problems of a person can be solved by healing the psychic condition through a method based on the Qur'an and Hadith. This study will explain Islamic perspective about the strategy of theistic spiritual in counseling and psychotherapy services to a person experiencing spiritual crisis (spiritual distress). This study concludes that in the counsseling and therapy services of Islam there are various strategies. One of them is the strategy of theistic spiritual with hypnocounseling. The strategy of theistic spiritual using hypnocounseling is the process of healing to psychological problems by optimizing the spiritual potential of man to awaken his existence in determining the meaning, value, morals and love of God and also fellow creatures. This strategy can be done by spiritual comunication with God, as well as reading al-Qur'an, prayer, dhikr, fasting, zakat, hajj and etc. By using this strategy, someone who is experiencing spiritual crisis problems is expected to be cured. However, it should be realized that not everyone can apply counseling and therapy counseling practice through hypnocounseling. This is because it needs special skills in applying it.